Mewujudkan Wisata Bedugul yang Aman melalui Edukasi Keselamatan untuk Pengemudi dan Penumpang - Mardikawati, Budi; Ramadhan, Sendy Fariz; Maharani, Rizky Caraka; Gunayasa, I Gusti Putu Adi; Anggayeni, Ni Putu Rika; Suari, Ni Putu Tatia Ardelia; Putri, Putu Ariestha Adelia; Krisnayanthi, Ni Komang Novia; Rokhim, Ihsan Nur (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2024)
Travel safety is a vital aspect of supporting the tourism industry, especially in popular destinations like Bedugul. This article discusses safety outreach and education efforts aimed at drivers and passengers in the Bedugul tourist area. This outreach activity aims to increase awareness and understanding of the importance of safe driving practices and passenger behavior that supports safety. Through a participatory and interactive approach, this program successfully conveys key information about safety procedures, the use of personal protective equipment, and handling emergency situations. The results of this activity show a significant increase in safety awareness among drivers and passengers, which is expected to reduce the risk of accidents and increase tourist comfort. This article concludes that ongoing safety education is the key to creating a safer and more enjoyable tourism environment in Bedugul.